Effect of different calcination duration on physicochemical properties of vanadium phosphate catalysts - Yun Hin Taufiq-Yap; Hwei Voon Lee; Yin Chang Wong; Kok Leong Theam; Wen Jiunn Tang (2012)
Vanadium phosphate catalysts have been prepared by calcining VOHPO44·0.5H2O which were prepared via two methods i.e. organic (VPO method) and dihydrate (VPD method) routes for different duration under anaerobic atmosphere. Increasing the calcinations duration led to a decrease in total surface area. It is also promote the formation of V5+ phase in the catalysts. Scanning electron microscopy clearly revealed that the morphologies of all catalysts composed of plate-like crystallites that were arranged into the characteristic of rosette cluster. However, by increasing the pretreatment duration in an inert environment, the rosette-shape of the clusters which normally obtained in reaction condition was collapsed. Prolong the duration of N2 calcination also resulted in an increment in the amount of oxygen desorbed (from O2-TPD) and removed (obtained from H2-TPR).